2018
DOI: 10.1002/jcb.26900
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‐486‐5p in regulating renal cell carcinoma cell proliferation and apoptosis via TGF‐β–activated kinase 1

Abstract: Renal cell carcinoma (RCC) is a common kidney tumor in adults. The role of miR-486-5p in RCC is unknown. The aim of our study was to identify new targets regulated by miR-486-5p in RCC, to obtain a deeper insight into the network and to better understand the role of these microRNAs and their targets in carcinogenesis of RCC. We performed a series of tests and found consistently lower expression levels of miR-486-5p in kidney cancer cells. Restoration of miR-486-5p expression in RCC cells could lead to the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…For instance, miR-486-5p can regulate the production and potentiate the growth of normal red blood cells, and it can mediate the drug response of chronic myeloid leukemia progenitor cells (Wang et al, 2015). Whereas in renal cell carcinoma, miR-486-5p is decreased by interacted with the CCL2 (C-C motif chemokine ligand 2) of tumor-related macrophages, and miR-486-5p restoration is capable of inhibiting cell proliferation and inducing cell apoptosis (He et al, 2019). However, the role of miR-486-5p in LUAD remains poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-486-5p can regulate the production and potentiate the growth of normal red blood cells, and it can mediate the drug response of chronic myeloid leukemia progenitor cells (Wang et al, 2015). Whereas in renal cell carcinoma, miR-486-5p is decreased by interacted with the CCL2 (C-C motif chemokine ligand 2) of tumor-related macrophages, and miR-486-5p restoration is capable of inhibiting cell proliferation and inducing cell apoptosis (He et al, 2019). However, the role of miR-486-5p in LUAD remains poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a CLDN10-associated ceRNA network was constructed in the present study, and the results revealed that miR-486-5p and miR-3919 may be the key regulators of CLDN10 expression in OC. Notably, miR-486 is reported to regulate cancer metastasis in hepatocellular carcinoma by targeting CLDN10, and miR-486-5p could inhibit cell proliferation and apoptosis in renal cell carcinoma via TGF-β-activated kinase 1 (44,45). Further investigations on the associations among CLDN10, miR-486-5p, miR-3919, TGF-β, WNT/β-catenin and EMT should be conducted in future studies, and could provide valuable insight on the cellular mechanisms underlying OC progression.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐486‐5p has been featured with multiple functions in different human cancers. It has been reported that miR‐486‐5p serves as a tumor suppressor in colorectal cancer, thyroid cancer, renal cell carcinoma, and non‐small cell lung cancer . However, it has also been reported that miR‐486‐5p functions as a tumor promoter in alveolar rhabdomyosarcoma and cervical cancer .…”
Section: Discussionmentioning
confidence: 99%